“Aquela que ficou presa” : os sentidos sobre o trabalho doméstico análogo à escravidão a partir da circulação midiática - Athaide, Lucilene Guimarães (Universidade do Vale do Rio dos Sinos, 2025)
This investigation proposes itself a reflection over the production of meanings related to domestic labor analogous to slavery in Brazil. Based on some observed evidence (Braga, 2008), the goal is to answer the following research question: what meanings are produced from media circulation of cases of domestic labor analogous to slavery in Brazil? And in what way does the journalism update and/or maintain stigmatizing frameworks in its productions, affecting the social debate over this theme? The following research is a mediatized case study (Weschenfelder, 2020) with ethnographic character (Weber, 2009; Silva, 2019, Verón, 1983) and it was made from two methodological movements: the theoretical-conceptual reflection and the empirical analysis with social actors. On the theoretical reflection, we dialogue with the fertile bibliographical production of the studies in mediatization and mediatized circulation (Carlón, 2020; Fausto Neto, 2018; Verón, 1980; Rosa, 2019) from an observable case: the story of Madalena Gordiano, black woman who was enslaved for over 40 years on the city of Patos de Minas, Minas Gerais state, and rescued in 2020. In the empirical analysis, we interviewed four black women who perform paid domestic labor, and who live in the Metropolitan Region of Porto Alegre, in Rio Grande do Sul state. Regarding the Madalena story, we intended to observe how was made the circulation of the journalistic event on different ambiences, just as their fraces, flows and bundles of relationships on the circuits through it was generated (Fausto, 2018; Verón, 1980, 2004). Related to the interviews, we chose to use a semi-structured questionnaire, preserving the identities of the interlocutors (Escosteguy, 2008; Weber, 2009). We propose, in this thesis, to understand circulation as a process that isn’t neutral, but it is immersed in a colonial logic, and also racist and patriarchal, and are arranged on the communicational flow. The circulation, far from being a product, is a space for the production and management of values that arise with mediatization, but that are structured outside the media, contributing to a certain extent to critical thinking and confrontation on the part of social actors. As a result, we identify mediatization as a process that expands the debate on the analogy to slavery beyond what is reported, with circulation, putting into perspective the individual trajectories of confrontation and protagonism, sometimes in a libertarian way, sometimes following the slave-owning social form of society (Sodré, 2023). Certainly, far from exhaust the debate, the intention is that the study helps to support other reflections about the themes of circulation, journalism, communication and gender, especially with regard to stereotypes about racialized people in the media.
Keywords: Circulação; Escravidão; Midiatização; Mulheres negras; Trabalho doméstico; Circulation; Slavery; Mediatization; Black women; Domestic work; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis